2014
DOI: 10.1016/j.jocrd.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Tourette syndrome: Insights from recent neuroimaging studies

Abstract: Tourette syndrome has been examined using many different neuroimaging techniques. There has been a recent surge of neuroimaging research papers related to Tourette syndrome that are exploring many different aspects of the disorder and its comorbidities. This brief review focuses on recent MRI-based imaging studies of pediatric Tourette syndrome, including anatomical, functional, resting state, and diffusion tensor MRI techniques. Consistencies across studies are explored, and particularly important issues invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…6,7 The largest studies were reported by Peterson and colleagues, with over 100 children and adults with TS and a similar number of control subjects. However, substantial questions remain about the structural anatomy of the brain in TS because methods and results have varied widely across studies, and because most studies were from small samples.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The largest studies were reported by Peterson and colleagues, with over 100 children and adults with TS and a similar number of control subjects. However, substantial questions remain about the structural anatomy of the brain in TS because methods and results have varied widely across studies, and because most studies were from small samples.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this background, our findings collectively support the construct validity of this TS model. The pathophysiological relevance of D1CT‐7 transgenic mice to TS symptoms is also supported by the recent discovery that TS patients display hyperactivity of the same sensorimotor circuit that is neuropotentiated in these mice (Campbell et al ., ; Bohlhalter et al ., ; Wang et al ., ; Church and Schlaggar, ); furthermore, it is worth noting that recent data indicated that in rodents the optogenetic stimulation of the cortex has been shown to produce features similar to symptoms of OCD – a highly co‐morbid syndrome with TS (Ahmari et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, developmental transcriptome analysis suggested that in adolescence, RICTOR is upregulated in the cerebellar cortex, striatum, and hippocampus. Structural neuroimaging studies have reported a reduction in the volume of the caudate nucleus, one of the striatal structures, in TS patients (Church & Schlaggar, ; Peterson et al, , ), and it has been suggested that smaller caudate volume in childhood correlates with the severity of persistent symptoms observed in adulthood (Bloch, Leckman, Zhu, & Peterson, ). Patients with TS, who are mostly children, demonstrate abnormal volume of the cerebellar cortex (Tobe et al, ) and hippocampus (Peterson, Choi, & Hao, ) and altered dopaminergic function in the hippocampus (Gilbert et al, ), whereas fMRI [Bohlhalter et al, ] and PET (positron emission tomography) (Lerner et al, ; Stern et al, ) have revealed that the cerebellum is involved in tic movements.…”
Section: Discussionmentioning
confidence: 99%